The Effect of Regional Tax Digitalization, Tax Knowledge, and Taxpayer Awareness, on Restaurant Taxpayer Compliance in Makassar City - Jamaluddin, Jamaluddin; Nujum, Syamsu; Selong, Abbas; Rahman, Zainuddin (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This research was conducted with the following objectives: (1). To find out and analyze the influence of regional tax digitization on mandatory compliance of restaurants in Makassar City. (2). To find out and analyze the influence of tax knowledge on the compliance of restaurant taxpayers in Makassar City. (3). To find out and analyze the influence of taxpayer awareness on the compliance of restaurant taxpayers in Makassar City The research method used in this study is descriptive analysis and Multiple Linear Regression analysis, with a sample of 79 Restaurant Taxpayers in Makassar City. Based on the results of multiple linear regression analysis, the results show that (1). The digitization of regional taxes has a positive and significant effect on the compliance of restaurant taxpayers in Makassar City. (2). Tax knowledge has a positive and significant effect on the compliance of restaurant taxpayers in Makassar City. (3). Taxpayer awareness has a positive and significant effect on the compliance of restaurant taxpayers in Makassar City.